CO2 adsorption study on primary, secondary and tertiary amine functionalized Si-MCM-41 - Ahmed, S. (Elsevier Ltd, 2016)
The present study was conducted to investigate the CO2 adsorption efficiency of siliceous mesoporous material known Si-MCM-41 and impacts of amine loading, amine type, CO2 pressure and adsorption temperatures on CO2 adsorption. Si-MCM-41 was impregnated with monoethanolamine (MEA), diethanolamine (DEA) and triethanolamine (TEA). The adsorption study was investigated from very low pressure to 1Â bar at three temperatures (i.e. 25, 50 and 75Â Â°C) in pure CO2 atmosphere. Pristine Si-MCM-41 shows maximum CO2 adsorption capacity of 27.78Â mg/g at 25Â Â°C and 1Â bar pressure. Monoethanolamine functionalized Si-MCM-41 with 10â50Â wt. samples were investigated in order to optimize MEA loading for maximum CO2 adsorption. The 50Â wt. MEA-Si-MCM-41 sample exhibited the highest CO2 adsorption capacity of 39.26Â mg/g at 25Â Â°C and 1Â bar pressure as compared to other samples. 50Â wt. DEA-Si-MCM-41 and 50Â wt. TEA-Si-MCM-41 samples were also investigated for their affinity to capture CO2 at the same conditions. Results show that 50Â wt. MEA-Si-MCM-41 still gives the highest CO2 adsorption capacity while adsorption capacity decreased in order of monoethanolamine, diethanolamine and triethanolamine-functionalized Si-MCM-41. CO2 adsorption capacity of all adsorbents decreases with increasing adsorption temperature above 25Â Â°C. Fourier transform infrared spectroscopy (FTIR) analysis of CO2-saturated 50Â wt. MEA, DEA and TEA-Si-MCM-41 samples shows the presence of transmission peaks associated to formation of carbamates. Â© 2016 Elsevier Ltd